Best Answer

3x + 12 = -7x - 28

First, move all variables to one side and numbers to the other. There are several different ways to begin, but let's move the 12 by subtraction from both sides.

3x = -7x - 40 is the new equation. Next, move the -7x to the left by addition to both sides.

10x = -40

Divide both sides by 10

x = -4

Q: 3x plus 12 equals -7x -28?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x + 8 = 2x +28 3x - 2x = 28 - 8 x=20

3x + 7 = -4x + 28 implies 7x + 7 = 28

x=-5

x = 5

2x-12

Related questions

3x + 8 = 2x +28 3x - 2x = 28 - 8 x=20

3x + 7 = -4x + 28 implies 7x + 7 = 28

x=-5

x = 5

2x-12

3x+8 = 12 3x = 4 x = 4/3

3x+42=6x+12 42=6x-3x+12 42=3x+12 42-12=3x 30=3x 10=x

Point slope equation: Y=3X+12

3x+12=x+48: 3x-x=-12+48 2x=36 x=18

3x - 12 = -2x + 235x = 35 so x = 7

7x = 3x - 12 4x=-12 x=-3

No.